Pengaruh Disiplin Kerja, Budaya Organisasi dan Lingkungan Kerja Non Fisik terhadap Produktivitas Kerja Pegawai Dinas Tanaman Pangan, Holtikultura dan Perkebunan Kota Sungai Penuh - Ferry Siswadhi; Yelnim (Syntax Corporation, 2023)
This research aims to know the influence of work discipline, organizational culture and nonphysical working environment against work productivity in food crops, holticulture and plantation department at sungai penuh city partially and simultaneous. Respondents to this study is The Food Crops, Holticulture and Plantation Department at Sungai Penuh City 43 people. Instrument in this study have passed the stage of test validity and reliability, by performing multiple linear regressaion test, statistical test, determination of koefesien F (simultaneous) and the test statistic t (partial). The result of the research there is influence between work discipline towards work productivity as evidenced by t hitung > t tabel (2,173 > 2,022) as well as the significance value = 0,036 < 0,05. There is the influence of organizational culture toward work productivity as evidenced by t hitung > t tabel (2,499 > 2,022) as well as the significance value = 0,017 < 0,05. There is the influence of nonphysical working environment against workproductivity as evidenced by t hitung > t tabel (4,910 > 2,022) as well as the significance value = 0,000 < 0,05. Simultaneously, work discipline, organizational culture and nonphysical working environment towards work productivity as evidenced by F hitung > F tabel (29,827 > 2,85) as well as the significance value = 0,000 < 0,05. Data analysis results showed big influence work discipline towards work productivity in persial of 15,67%, large influence organizational culture towards work productivity in persial amounted to 17,47% and great nonphysical working environment towards work productivity in persial of 36,42%. Data analysis results showed big influence work discipline, organizational culture and nonphysical working environment toward work productivity simultaneously of 69.7%.